MODEL SISTEM MULTI AGEN LINEAR DENGAN FORMASI SEGITIGA - Tjahjana, Redemtus Heru (MATEMATIKA, 2010)
In this paper, a linear model of multi agent movement in equilateral triangle formation is considered. The agents have initial and final state in triangular formation. Along the motion, all agents can not move far away and collide. The agents are steered from initial position to final position in fixed time. For this goal, optimal control with Pontryagin Maximum PrincipleÂ  is applied and the classic difficulty in the optimal control problem is appear. To solve the classic difficulty above, the steepest descent method is used.